Battlestar Galactica. Season 3 [videorecording (DVD)] - Larson, Glen A.; Rymer, Michael, 1963-; Moore, Ronald D.; Olmos, Edward James; McDonnell, Mary; Sackhoff, Katee; Bamber, Jamie, 1973-; Callis, James; Helfer, Tricia; Bennett, Matthew, 1954-; Stockwell, Dean, 1938- (Universal Studios Home Entertainment, 2008)
The Colonies' survivors have found their hopes of eluding their Cylon pursuers dashed by an invasion and occupation of their new home. As the fate of all human life hangs in the balance, friends become enemies, enemies become unexpected allies, and decisions are made that will haunt some people for the rest of their lives.